2020
DOI: 10.1016/j.psychsport.2020.101668
|View full text |Cite
|
Sign up to set email alerts
|

The effect of unilateral hand contractions on psychophysiological activity during motor performance: Evidence of verbal-analytical engagement

Abstract: Objectives: Conscious engagement in movement control can influence motor performance.In most cases, the left hemisphere of the brain plays an important role in verbal-analytical processing and reasoning, so changes in the balance of hemispheric activation may influence conscious engagement in movement. Evidence suggests that unilateral hand contractions influence hemispheric activation, but no study has investigated whether there is an associated effect of hand contractions on verbal-analytical processing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(36 citation statements)
references
References 46 publications
(100 reference statements)
1
12
0
Order By: Relevance
“…They did not find any difference in the emotional perception of photographs from either unilateral (intrahemispheric) or bilateral (interhemispheric) hemispheres as a function of hand contraction. Our findings also compare well with those of Hoskens et al (2020), who reported that contralateral hemisphere activity was revealed for left-versus right-hand contraction conditions. Specifically, left-hand contractions rather than right-hand contractions led to significantly lower T7-Fz connectivity, indicating brain regions involved in conscious engagement in movement control and motor performance during motor planning.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…They did not find any difference in the emotional perception of photographs from either unilateral (intrahemispheric) or bilateral (interhemispheric) hemispheres as a function of hand contraction. Our findings also compare well with those of Hoskens et al (2020), who reported that contralateral hemisphere activity was revealed for left-versus right-hand contraction conditions. Specifically, left-hand contractions rather than right-hand contractions led to significantly lower T7-Fz connectivity, indicating brain regions involved in conscious engagement in movement control and motor performance during motor planning.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we investigated the effects of dynamic handgrip on perceptual-motor task performance by assessing speed (RT) and accuracy (error rate) of the response to stimuli in SRT and CRT tasks in the final cohort of 64 right-handed participants. Previous neural and behavioral studies found prevention of performance decrements or even increases in performance on motor tasks with dynamic handgrip (Beckmann et al 2013;Hoskens et al 2020). However, RTs and error rates in perceptual-motor tasks have not yet been addressed with this embodiment technique.…”
Section: Discussionmentioning
confidence: 96%
“…However, EEG studies [21,22] showed that the hand clenching does not produce a shift of activation from the left to the right brain hemisphere but triggers relaxation (high alpha wave) that spreads across the whole cortex, producing a state of reduced cortical activity in the left brain hemisphere. In line with this, Hoskens et al [23] argue that an engagement in movement control is associated with verbal-analytical processing (i.e., the planning and reasoning of an action framed in words). They further show that unilateral hand contractions influence the extent of this verbal-analytical engagement during motor planning, which in turn influences motor performance.…”
Section: Introductionmentioning
confidence: 94%
“…Of the five studies that examined performance accuracy, two found lower T7-Fz connectivity for more accurate performance (Cheng et al, 2017;, and three found no difference between accurate and inaccurate performances (Dyke et al, 2014;Hunt et al, 2013;van Duijn et al, 2017). One study experimentally decreased T7-Fz using pre-performance hand contractions, but this had no significant effect on performance or kinematics (Hoskens et al, 2020).…”
Section: Ispc Imispcmentioning
confidence: 99%
“…Other studies used verbal recall protocols that asked participants what they were thinking about during the task (Daou et al, 2018;van Duijn et al, 2019;Zhu et al, 2011a, exp. 2), eye tracking to correlate EEG activity and eye movement behaviors (Parr et al, 2019) and measures of cardiac activity as markers of conscious control (Bellomo et al, 2020). Despite conscious control being related to changes in movement kinematics (e.g., increased movement jerk and slower movements) only three studies used kinematics to show how verbal processing impacted upon movement control (i.e., Bellomo et al 2020;Parr et al, 2020;Hoskens et al, 2020). While the adoption of such methods is encouraging, it is clear that a large proportion of work in this area simply infers verbal processing from left-temporal alpha activity coupled with poorer learning and performance.…”
Section: Secondary Measures Of Verbal and Conscious Processingmentioning
confidence: 99%